Association study between HTR2A rs6313 polymorphism and early response to risperidone and olanzapine in schizophrenia patients. Issue 6 (27th May 2020) - Maffioletti, Elisabetta; Valsecchi, Paolo; Minelli, Alessandra; Magri, Chiara; Bonvicini, Cristian; Barlati, Stefano; Sacchetti, Emilio; Vita, Antonio; Gennarelli, Massimo
Abstract: Antipsychotic drugs are the preferred choice for schizophrenia treatment; however, response is highly variable. In the context of the search for predictors of antipsychotic treatment effectiveness, the evaluation of response within 2 weeks has been indicated to predict long‐term outcome. Moreover, a focus on symptomatological domains could be helpful to better characterize antipsychotic response, identifying more specific predictors. Pharmacogenetic studies have indicated a role for rs6313 in the serotonin receptor gene HTR2A in affecting response to antipsychotics, with heterogeneous results. With the aim to test for the first time the application of a dimensional approach for the evaluation of early response, we carried out a genetic association study between rs6313 and antipsychotic response in two groups of schizophrenia patients in monotherapy with risperidone ( n = 121) and olanzapine ( n = 100). Patients were evaluated at the baseline and after 1 and 2 weeks of treatment. When comparing early responders versus early nonresponders, no association was detected for the two drugs separately, whereas by taking into consideration the two drugs together it was observed that carriers of the T allele had a higher response probability compared to noncarriers. Considering 2‐week improvements, changes in PANSS total scores, subscores and in PANSS Emsley's symptomatological dimensions were associated with rs6313 for both risperidone and olanzapine. Moreover, the repeated measures analysis indicated an association of rs6313 with the disorganized thought dimension for risperidone, and with the depressive and anxiety dimensions for olanzapine. These data add support to the hypothesis that the HTR2A gene is involved in antipsychotic treatment outcome.